Outlaw fathers in Victorian and modern British literature : queering patriarchy - Gurfinkel, Helena (Fairleigh Dickinson University Press ; Rowman and Littlefield, 2013)
Outlaw Fathers provides an innovative reading of fatherhood and father-son relationships in a number of Victorian and modern literary texts. In addition to using an inventive psychoanalytic paradigm for redefining, or queering, the concept of patriarchy in literary studies and theory, it joins a larger contemporary conversation about changing masculinities and families.